Energy Saving Algorithm of Wireless Network Nodes in Cluster - Zhang, Zihong; Luo, Rui; Fu, Wei (International Wireless Communications and Mobile Computing Conference (Online), 2020)
Firstly, this paper analyzes the technology system and characteristics of the Internet of things. Secondly, the paper mainly studies the intelligent algorithm of data transmission in the Agricultural Internet of things. According to the different energy efficiency and the limited battery capacity of rechargeable sensor nodes, a new clustering routing protocol is proposed. Meanwhile, in order to solve the problem of fault-tolerant routing repair and maintain the quality of fault-tolerant routing, the paper proposes a new routing strategy (CR-WSN). Compared with the CRAS algorithm, they have the same point that a node with more remaining energy is selected as the cluster head node, but the energy consumption ratio of CR-WSN is significantly better than CRAS. Therefore, CREW can achieve the purpose of reducing energy consumption and improving link fault tolerance.